2014
DOI: 10.1063/1.4900695
|View full text |Cite
|
Sign up to set email alerts
|

Resistive states in wide superconducting films induced by dc and ac currents (Review Article)

Abstract: This review is devoted to the studies of the resistive state in wide superconducting films induced by dc and ac currents in the absence of an external magnetic field. It is found experimentally that the current-voltage characteristics and their parameters are well described by the Aslamazov–Lempitskii theory of the resistive vortex state, which has long been lacking an adequate evidence to support it. There is experimental evidence that the vortex mechanism of resistivity is absent for currents exceeding the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Given the fact that our strips are considerably wider than the coherence length and very close to the SIT, such agreement is very satisfactory. It suggests that the concept of thermally activated phase slips (in our case, more phase slip lines [28]) can at least qualitatively be transferred to films substantially wider than the coherence length [29].…”
Section: A Temperature Dependence Of Resistancementioning
confidence: 77%
“…Given the fact that our strips are considerably wider than the coherence length and very close to the SIT, such agreement is very satisfactory. It suggests that the concept of thermally activated phase slips (in our case, more phase slip lines [28]) can at least qualitatively be transferred to films substantially wider than the coherence length [29].…”
Section: A Temperature Dependence Of Resistancementioning
confidence: 77%
“…, where κ * is constant of order 1 [19] and N 0 is the number density at the Fermi level. However, if the trace is wider than the perpendicular penetration depth w λ ⊥ , the current distribution becomes non-uniform and accumulates at the edges of the film [16]. In this work, the SC traces are in the 100s µm which means solutions of the wide film critical current should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The scaling current is sensitive to a number of factors [16] including the substrate roughness and composition, film geometry, deposition conditions and operating temperature which means it can vary over orders of magnitude for a given SC material. Analytic solutions of the scaling current usually only set the upper bound for this value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it was argued that the one-to-one mapping of a vortex to a particle breaks down at high velocities where vortex displacements take place at shorter time scales than the time to recover the superconducting order parameter along the vortex trajectory. The vortices then become elongated and turn into phase slip lines [17,100,[110][111][112]. While it has been demonstrated that vortex guiding persists up to several GHz [57], the crossover from the vortex-mediated flux transport to that via phase slips should be elaborated.…”
Section: Perspectivementioning
confidence: 99%